Bit-Slicing the Hilbert Space: Scaling Up Accurate Quantum Circuit Simulation - Tsai, Yuan-Hung; Jiang, Jie-Hong R.; Jhang, Chiao-Shan (2021 58th ACM/IEEE Design Automation Conference (DAC), 2021)
Recent advancements in quantum technologies shed light on viable quantum computation in near future. Quantum circuit simulation plays a key role in the toolchain of quantum hardware and software development. Due to the enormous Hilbert space of quantum states, simulating quantum circuits with classical computers is notoriously challenging. This work enhances quantum circuit simulation in two dimensions: accuracy (by representing complex numbers algebraically) and scalability (by bit-slicing number representation and achieving matrix-vector multiplication with symbolic Boolean manipulation). Experiments demonstrate the superiority of our method to the state-of-the-art tools over various quantum circuits with up to tens of thousands of qubits.